(untitled) (Annals of Medical Research, 2021)
Aim: Ventricular repolarization were evaluated in patients who had POF by using novel electrocardiographic parameters including Tpe-interval and Tpe/QT and Tpe/QTc ratios. A few studies have investigated the association between premature ovarian failure (POF) and cardiovascular diseases. However, none have examined ventricular repolarization in this respect.Materials and Methods: This cross-sectional study included 60 female patients with POF (mean 32.6±4.7 years) and 54 control healthy female subjects (mean 30.9±4.6 years).All electrocardiogram (ECG) measurements were performed by a cardiologist using a computer, and the Tpe-interval, Tpe/QT, and Tpe/QTc were compared between groups.Results: There were no significant differences between groups in terms of baseline characteristics and laboratory parameters. The Tpe-interval, Tpe/QT, and Tpe/QTc were significantly prolonged in POF group than control subjects (p0.001 for all). There was a strong and positive correlation between the serum follicle-stimulating hormone (FSH) level and Tpe-interval (r=0.681; p0.001) and Tpe/QTc (r= 0.636; p0.001). Furthermore, high and negative correlation was found between serum estradiol and Tpe-interval (r=-0.531; p0.001) and Tpe/QTc (r=-0.510). Multivariate linear regression analysis showed that that the FSH and estradiol level were independent predictors of both the Tpe-interval (B=0.541 and p0.001, B=-0.202 and p0.001, respectively) and Tpe/QTc (B=0.442 and p0.001, B= -0.239 and p0.001, respectively).Conclusion: It was concluded in the study that ECG parameters of ventricular repolarization, namely, Tpe-interval, Tpe/QT, and Tpe/QTc were significantly prolonged in patients that had POF.